A clinical study comparing the accuracy of the clinical examination, ultrasonography, fine needle aspiration cytology with that of histopathology - Abbaraju, Sasidhara Rao; Sridhar, Punyapu; Kota, Sameera; Farooqi, Zainab; Panguluru A. S., Nikhil Mehra (International Surgery Journal, 2022)
Background: Fine needle aspiration cytology (FNAC) is considered the gold standard diagnostic test for the diagnosis of thyroid nodules. FNAC is a cost-effective procedure that provides specific diagnosis rapidly with minimal complications. Aims was to compare efficacy of Clinical diagnosis, ultrasonography (USG), FNAC with one another and with that of histopathological examination (HPE) diagnosis. Methods: It is a prospective comparative study in 60 patients admitted with thyroid swellings in the department of General Surgery were taken for study purpose. The clinical diagnosis, ultrasonogram report, FNAC and HPE were included in the study. Results: Thyroid disease is 4.54 times more common in females. Thyroid disease is more common in the reproductive age group with the mean average age of 37.91±11.02 years. The male:female sex ratio for carcinoma is 1:2.33. Benign thyroid disorders constitute 83.3% of the total thyroid disorders. The overall efficacy of FNAC (88.33%) is far higher than USG (76.66%) and clinical diagnosis (56.66%). Sensitivity for diagnosis of thyroiditis clinically is very poor (45.45%) as compared to diffuse goiter (71.43%). FNAC can reasonably differentiate benign from malignant lesion most of the time with sensitivity of about 90%. Conclusions: Ultrasonogram alone cannot correctly diagnose different types of benign lesions with accuracy. However, it can most of the time differentiate benign from a malignant lesion. It has an overall efficacy of 76.7%. The efficacy of FNAC is nearly 90% making it an essential diagnostic tool for diagnosing thyroid disease.